NOVEL AND REFIGURING LIFE - Setyadi, Wawan (International Journal of Humanity Studies (IJHS), 2019)
This article explores the confluence between novel and the life of its reader in two phases. Firstly, this article examines the theory of mimesis of Paul Ricœur in Time and Narrative I to arrive at the importance of the reading act where the reader does his own appropriation of the novel read. The novel itself is a creative composition based on the daily human actions. Secondly, this article deciphers the work of Milan Kundera, especially his concept of existential code, found in the novel The Unbearable Lightness of Being and sharpened by his concept of writing novels in The Art of the Novel. This second phase gives another articulation of the first phase, which is more philosophically theoretical. Based on these two phases of exploration, this article uncovers the refigured man who comes to understand both himself and the world he lives in better and who has new different propositions and possibilities to live better as well.DOI: 10.24071/ijhs.2019.020201